Noninvasive estimation of mixed venous oxygen content - Katsuo Uchida (Japanese Society of Physical Fitness and Sports Medicine, 2014)
Mixed venous and arterial oxygen content (CvO2 and CaO2) are fundamental factors to connect cardiac output and oxygen uptake by the Fick principle. Direct measurements of CaO2 and CvO2 require blood samplings and quantifications of the oxygen contents. Arterial blood can be sampled from a peripheral artery, but a right cardiac catheter is necessary for mixed venous blood sampling. Moreover, quantifications of the blood oxygen contents are complicated compared with those of blood oxygen partial pressures. Accordingly, indirect methods to estimate CaO2 and CvO2 have been developed. CaO2 can be evaluated as the sum of chemically and physically dissolved oxygen in arterial blood. If mixed venous blood is sampled, CvO2 can be obtained from mixed venous oxygen saturation and partial pressure as well. As for noninvasive methods without blood samplings, arteriovenous oxygen difference (CaO2 - CvO2) was obtained from a relationship between respiratory exchange ratio and carbon dioxide partial pressure during rebreathing. Recently, we developed another noninvasive method to estimate CvO2 from SpO2 and heart rate with a pulse oximeter, and obtained an equation CaO2 - CvO2 (vol%) = -0.265×10-6h2 + 0.289×10-3h + 7.74 with altitude h in meters. In this review, these two noninvasive methods, rebreathing and pulse oximeter, are discussed.